Centralization of cleft care in the UK. Part 6: a tale of two studies. (November 2015) - Ness, A. R.; Wills, A. K.; Waylen, A.; Al‐Ghatam, R.; Jones, T. E. M.; Preston, R.; Ireland, A. J.; Persson, M.; Smallridge, J.; Hall, A. J.; Sell, D.; Sandy, J. R.
Structured Abstract: Objectives: We summarize and critique the methodology and outcomes from a substantial study which has investigated the impact of reconfigured cleft care in the United Kingdom (UK) 15 years after the UK government started to implement the centralization of cleft care in response to an earlier survey in 1998, the Clinical Standards Advisory Group (CSAG). Setting and Sample Population: A UK multicentre cross‐sectional study of 5‐year‐olds born with non‐syndromic unilateral cleft lip and palate. Data were collected from children born in the UK with a unilateral cleft lip and palate between 1 April 2005 and 31 March 2007. Materials and Methods: We discuss and contextualize the outcomes from speech recordings, hearing, photographs, models, oral health and psychosocial factors in the current study. We refer to the earlier survey and other relevant studies. Results: We present arguments for centralization of cleft care in healthcare systems, and we evidence this with improvements seen over a period of 15 years in the UK. We also make recommendations on how future audit and research may configure. Conclusions: Outcomes for children with a unilateral cleft lip and palate have improved after the introduction of a centralized multidisciplinary service, and other countries may benefit from this model. Predictors of early outcomes are still needed, and repeated cross‐sectional studies, larger longitudinal studies and adequately powered trials are required to create a research‐led evidence‐based (centralized) service.